2019
DOI: 10.1111/jtxs.12466
|View full text |Cite
|
Sign up to set email alerts
|

The effect of modified starches on the gel properties and protein conformation of Nemipterus virgatus surimi

Abstract: The study investigated the effect of native cassava starch (NCS), hydroxypropylated starch, acetic acid esterification starch (AAES), acetylated distarch phosphate on gel properties and protein conformation of Nemipterus virgatus surimi. Addition of 10 g kg−1 NCS or 20 g kg−1 AAES could significantly promote the gel strength and textural profiles of the surimi gels (p < .05). The water holding ability and whiteness of surimi were remarkably increased when the four types of starch were added at all concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 31 publications
7
33
2
Order By: Relevance
“…Hydrophobic interactions predominate in the gel matrix compared with other non-covalent bonds [ 17 ], which are produced by the unfolding action of the protein (above 60 °C) and the exposure of the hydrophobic core. With an increase in starch content, hydrophobic interactions declined in CG ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Hydrophobic interactions predominate in the gel matrix compared with other non-covalent bonds [ 17 ], which are produced by the unfolding action of the protein (above 60 °C) and the exposure of the hydrophobic core. With an increase in starch content, hydrophobic interactions declined in CG ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Overall, these weak forces uniformly increased with the increment of starch content, containing non-specific associations, ionic bonds, and hydrogen bonds (p < 0.05). Hydrophobic interactions predominate in the gel matrix compared with other noncovalent bonds [17], which are produced by the unfolding action of the protein (above 60 • C) and the exposure of the hydrophobic core. With an increase in starch content, hydrophobic interactions declined in CG (Table 2).…”
Section: Scanning Electron Micrographmentioning
confidence: 99%
See 2 more Smart Citations
“…These results were consistent with above results in the present work. Previous studies also reported that the addition of starch resulted in the formation of better gel network (Sun et al ., 2014; Mi et al ., 2019). The ability of starch to induce myosin aggregation might partly account for the observed effect.…”
Section: Resultsmentioning
confidence: 99%